Bilinguialism: a key tool in the university context (2013)
This study constitutes a critical reflection with sociocultural approach on the need to rethink the bilingualism in higher education. Its main purpose is focus on the understanding of the current education as a multilingual practice in the context of the knowledge society. It is structured from the Popular University of Cesar as a case for the analysis and development from the qualitative methodology of social research, in order to understand the way in which the actors interpret and construct their own meanings and situations within and outside the classroom. It addresses key aspects of bilingualism and multilingualism such as political action, socioeconomic and labor relations and training of various professions. As a result it is concluded that the functional use of foreign languages involves a negotiation of meaning from the relationship of language, culture and thought.